Spatio-temporal resource utilization by a Bornean rainforest herpetofauna: Preliminary results - Das, I. (Kluwer Academic Publishers, 1996)
Field work was conducted on the community organization of the herpetofauna at Batu Apoi Forest Reserve, a lowland mixed dipterocarp forest in Brunei Darussalam. The present communication is a preliminary analysis of the patterns of utilisation of microhabitat and diel-time resources by the more abundant species of amphibians and reptiles at the study site. A total of fifty-two species of amphibians and forty-six species of reptiles were recorded, both faunas composed of a species-poor riparian and a species-rich non-riparian assemblage. Several species recorded at the Reserve are frequently human commensals, and therefore indicators of disturbed habitats. Human activities tend to create new niches or expand existing ones that are rapidly filled by these weed species associated with man. Analysis of the microhabitat and diel-time reveal that the non-riparian assemblage has more space and time-specialists than the riparian one. It is concluded that high diversity is maintained in the more climatically-stable forested zones by species specializing in the use of both microhabitat and diel-time.